DISTRIBUCION DE SYSTOLE CORIANDRI (GUSSAKOVSKI) (HYMENOPTERA: EURYTOMIDAE) Y EVALUACION DEL DAÑO EN SEMILLAS DE CILANTRO, CORIANDRUM SATIVUM L. (UMBELLIFERAE), EN CHILE - Lamborot, Lilianne; Paredes, Félix R.; Arretz, Patricio; Guerrero, M. Angélica; Araya, Jaime E. (Acta Entomológica Chilena, 2022)
Seed samples of coriander, Coriandrum sativum L., infested by Systole coriandri (Gussakovski) (Hymenoptera: Eurytomidae) were obtained during 1985-87 from locations in the lst, 5th, 6th, 8th, 9th, and Metropolitan regions of Chile. Infestation varied yearly and among localities, from no infestation in Puangue (Metropolitan Región), which presents frequent and strong winds, to 49.5% and 60.3% damaged seeds in Quillota (5th Región) in 1985-86 and 1986-87, respectively. Azapa (lst Región), Noviciado, Lampa, and Pudahuel (Metropolitan Región) also had high infestation levels. Cultivation of coriander in the same field for two consecutive seasons increased the infestation of the seeds. A sample from Perú had 1.47% damaged fruits, some of which contained dead S. coriandri adults. Correspondence with 65 foreign research centers allowed adding Sweeden to the list of countries with 5. coriandri.